Textbooks as instruments – three teachers’ way to organize their mathematics lessons - Johansson, Monica (NOMAD Nordic Studies in Mathematics Education, 2006)
This paper reports a study of three teachers’ way to organize their lessons and how textbooks are incorporated in their work1. Despite the differences between the teachers, it is noticeable that in these three classrooms, the textbooks, to a large degree, guide the teaching. The textbooks are present: (a) in the students’ individual work, (b) in many of the examples presented on the board, (c) as a source for background and motivational discussions, (d) in how mathematics is presented, and (e) for homework.